KOLABORASI MUHAMMADIYAH DALAM KANCAH INTERNASIONAL:BERGURU ISLAM KE BARAT DAN PENGEMBANGAN PERGURUAN TINGGI ISLAM DI INDONESIA - Yuliani, Yuliani; Mardianis, Mardianis; Yuliarni, Yuliarni; Julhadi, Julhadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This paper examines the international collaboration of Muhammadiyah in sending lecturers from Islamic Higher Education Institutions (PTKI) to Western universities as a strategy to improve the quality of Islamic education in Indonesia amidst globalization challenges. Using a qualitative descriptive approach, the study explores the historical context and rationale behind the policy, as well as the contributions of alumni to curriculum reform, research, global networks, and religious diplomacy. The findings suggest that the policy aims to integrate knowledge and faith in line with Islam Berkemajuan (Progressive Islam). The study concludes that sending PTKI lecturers abroad is not Westernization but a strategic effort to integrate knowledge and faith. Recommendations include strengthening co-funding policies, integrating interdisciplinary knowledge, and establishing collaborative research centers to prevent brain drain.